Multiple congenital anomalies-hypotonia-seizures syndrome 3 secondary to phosphatidylinositol glycan class T mutation: a neonatal case report - Ranjan, Ankit; Alam, M. Shahbaz; Kumar, Vinod; Samanta, Snigdha; Kumar, Rajesh; Saifullah , Khalid M. (International Journal of Contemporary Pediatrics, 2023)
Multiple congenital anomalies-hypotonia-seizures syndrome 3 (MCAHS3) is caused by genetic defects in glycosyl-phosphatidylinositol transamidase complex synthesis due to mutations in the PIGT gene. The disease encompasses dysmorphism, cardiac, genito-urinary and skeletal anomalies, developmental delay and epilepsy in variable severity. Only 39 such cases have been reported till date in literature. We reported the first Indian case with neonatal presentation and overall the sixth case of MCAHS3 to present in neonatal age. The pro-band was a male baby born to non-consanguineous parents. He had perinatal depression, craniofacial dysmorphism, epileptic encephalopathy, left radio-ulnar congenital fractures and respiratory failure managed with multiple anti-epileptics, invasive ventilation and limb splinting. Clinical exome sequencing revealed an autosomal recessive homozygous PIGT gene mutation on exon 6 of chromosome 20 with a variant nomenclature of C.709G>C with heterozygous parents confirming MCAHS3. This report expands the range of information available on MCAHS3. It highlights the need to elaborately investigate dysmorphic newborns with severe hypotonia along with the described neurological symptoms, so as to pin point this potentially diagnosable entity.